THE INFLUENCE OF LIVE STREAMING ENGAGEMENT ON CONTINUOUS WATCHING INTENTION WITH ELECTRONIC-WORD OF MOUTH AS A MODERATING VARIABLE - Rudy Irwansyah; Yeheskial Nggandung; Evaf Maulina; Cahyo Adi Nugroho; Efa Irdhayanti (ITB AAS Indonesia Surakarta, 2024)
This research is quantitative research with an exploratory approach which uses a number of previous studies as a reflection of the old to form an element of novelty in future research . The data that researchers used was obtained from 300 Muhammadiyah students spread throughout Indonesia who already had smartphones. The data obtained was distributed through an online questionnaire containing 5 choices of statements for questions, namely statements of strongly agree, agree, disagree, strongly disagree, and normal/so-so. The data used was analyzed using the Samrt PLS 4.0 analysis tool. The result in this article show the Live Streaming Engagement variable can have a positive relationship and a significant influence on Continuous Watching Intention. This can be proven because the P-Values value is positive and is below the 0.05 significance level, namely 0.006. . This is because Live Streaming's collaboration can make live creativity continue to increase with new innovations and new objects that can make live streaming viewers not bored and decide to watch live continuously. Apart from the results of the first hypothesis above, in the second row of the third table the path coefficients in this study show similar results if the Electronic-Word of WOuth variable can moderate the influence of the Live Streaming Engagement variable on Continuous Watching Intention because the P-Values value is positive and is at below the significance level of 0.05, which is 0.000, is more significant than the direct assessment of 0.006. Thus the first and second hypotheses in this research can be accepted. Keywords: Live Streaming Engagement, Continuous Watching , Electronic-Word Of Mouth